2006
DOI: 10.1097/01.brs.0000202807.72292.a8
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Subgroups of Patients With Acute/Subacute “Nonspecific” Low Back Pain

Abstract: Nonspecific low back pain should not be viewed as a homogenous condition. Outcomes can be improved when subgrouping is used to guide treatment decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
311
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 409 publications
(327 citation statements)
references
References 53 publications
10
311
0
6
Order By: Relevance
“…While many interventions have been dismissed as either ineffective or accompanied with small effect sizes, 80 recent reports in the literature suggesting that interventions based on sub-group classification have the potential to enhance effect sizes over studies where the identical interventions administered in a one-size fits-all approach. 34, 49, 105, 118, 199 …”
Section: Clinical Guidelines: Impairment/function-based Diagnosismentioning
confidence: 99%
See 3 more Smart Citations
“…While many interventions have been dismissed as either ineffective or accompanied with small effect sizes, 80 recent reports in the literature suggesting that interventions based on sub-group classification have the potential to enhance effect sizes over studies where the identical interventions administered in a one-size fits-all approach. 34, 49, 105, 118, 199 …”
Section: Clinical Guidelines: Impairment/function-based Diagnosismentioning
confidence: 99%
“…For patients who have had low back pain for > 6 months and/or for patients who have recurring low back pain, this clinical guideline promotes categorizing acute, sub acute, and chronic low back pain based on movement/pain relations rather than solely using time since the patient’s initial onset of low back pain. Movement/pain relations are commonly used in physical therapy for classifying patients into treatment categories that respond best to matched interventions strategies 33, 86, 99, 101, 103, 104 as well to guide dosing of manual therapy, therapeutic exercise, and patient education interventions. 172 The dosing of interventions based upon movement/pain relations is consistent with the concept of tissue irritability and is important for guiding the clinical decisions regarding treatment frequency, intensity, duration, and type with the goal of matching the optimal dosage of treatment to the status of the tissue being treated.…”
Section: Clinical Guidelines: Impairment/function-based Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…However, these validation studies did not address validity in subjects with leg pain. Brennan et al [9] demonstrated improved outcomes when treatment was matched to subjects' subgroups, defined as manipulation, stabilization and specific exercise according to criteria based on those proposed by Delitto et al [7]. As patients with signs of nerve root compression were excluded from this study, no conclusions can be drawn about this group of patients.…”
Section: Introductionmentioning
confidence: 95%